A one health approach to improve the safety of traditional yak blood drinking in Nepal - Krishna Prasad Acharya; Sarita Phuyal; AbdulRahman A. Saied (Communications Medicine)
Fresh yak blood drinking, which occurs in Nepal, may transmit zoonotic infections. Here, we discuss how a One Health approach involving local government, public health officials and community organizers may be applied to enable this tradition to continue more safely.